2020
DOI: 10.2196/16972
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Electronic Health Interventions in Improving Treatment Adherence for Adults With Obstructive Sleep Apnea: Meta-Analytic Review

Abstract: Background Poor adherence to continuous positive airway pressure (CPAP) treatment by adults with obstructive sleep apnea (OSA) is a common issue. Strategies delivered by means of information and communication technologies (ie, electronic health [eHealth]) can address treatment adherence through patient education, real-time monitoring of apnea symptoms and CPAP adherence in daily life, self-management, and early identification and subsequent intervention when device or treatment problems arise. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 44 publications
2
53
0
Order By: Relevance
“…In pulmonology, an improvement of the subscale CCQ symptom score was found after participating in an eHealth platform for a prospective COPD study in a blended care setting [ 20 ]. In a meta-analysis about the effectiveness of eHealth intervention in Obstructive Sleep Apnea (OSAS) no difference was found between studies using eHealth as an add-on to care as usual and studies using eHealth as a replacement of care as usual [ 21 ]. The nightly use of CPAP (adherence) increased, with eHealth interventions compared to care as usual, regardless of the involvement of a healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonology, an improvement of the subscale CCQ symptom score was found after participating in an eHealth platform for a prospective COPD study in a blended care setting [ 20 ]. In a meta-analysis about the effectiveness of eHealth intervention in Obstructive Sleep Apnea (OSAS) no difference was found between studies using eHealth as an add-on to care as usual and studies using eHealth as a replacement of care as usual [ 21 ]. The nightly use of CPAP (adherence) increased, with eHealth interventions compared to care as usual, regardless of the involvement of a healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
“…Some study results suggest that the use of telemonitored CPAP compliance and efficacy data seems to be as good as standard care in its effect on compliance rates and outcomes in new CPAP users, although conflicting data remain. 10,96,97 However, the results from other RCTs regarding improvement in compliance are disappointing (Table 3), given many studies do not show any improvement in compliance with telemonitoring. In contrast, in some of these studies, despite the application of telemonitoring, compliance remained extremely low, questioning the level of usual care in these centers.…”
Section: Fine Tuning Of Continuous Positive Airway Pressure Devices: Responsibilitiesmentioning
confidence: 99%
“…In the past few years, a big step forward has been made with the introduction of telemonitoring and technological strategies that allow remote assistance and provide a supporting network among patients and all involved professionals [60]. Indeed, recent studies have showed the effectiveness of telehealth in improving access to care and patient's outcomes [61][62][63].…”
Section: Long-term Noninvasive Ventilationmentioning
confidence: 99%